2020
DOI: 10.3390/pr8091071
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for the Classification of Alzheimer’s Disease and Its Prodromal Stage Using Brain Diffusion Tensor Imaging Data: A Systematic Review

Abstract: Alzheimer’s disease is notoriously the most common cause of dementia in the elderly, affecting an increasing number of people. Although widespread, its causes and progression modalities are complex and still not fully understood. Through neuroimaging techniques, such as diffusion Magnetic Resonance (MR), more sophisticated and specific studies of the disease can be performed, offering a valuable tool for both its diagnosis and early detection. However, processing large quantities of medical images is not an ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 69 publications
2
18
0
Order By: Relevance
“…Based on results emerging in the present analysis, we can conclude that our ensemble classification framework, based on DTI features, is effective to improve HC/AD classification performances, and that ensembles including FA and MD are the best performing, confirming their role in the literature as most effective DTI measures for AD detection [57][58][59][60]. Moreover, although artificial data balancing attenuates the benefits of ensemble learning, the ensemble-based strategy generates significant improvements in the classification sensitivity and accuracy with respect to the general concatenation of all features into a high-dimensional vector.…”
Section: Discussionsupporting
confidence: 73%
“…Based on results emerging in the present analysis, we can conclude that our ensemble classification framework, based on DTI features, is effective to improve HC/AD classification performances, and that ensembles including FA and MD are the best performing, confirming their role in the literature as most effective DTI measures for AD detection [57][58][59][60]. Moreover, although artificial data balancing attenuates the benefits of ensemble learning, the ensemble-based strategy generates significant improvements in the classification sensitivity and accuracy with respect to the general concatenation of all features into a high-dimensional vector.…”
Section: Discussionsupporting
confidence: 73%
“…An additional systematic review was identified through checking the list of the included reviews. In total, 15 systematic reviews were included in the current review [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] .…”
Section: Search Resultsmentioning
confidence: 99%
“…Several studies have proposed machine learning approaches for the classification of MCI and AD ( Gray et al, 2012 ; Wee et al, 2012 ; Nozadi et al, 2018 ; Billeci et al, 2020 ; Shi and Liu, 2020 ; Syaifullah et al, 2020 ; Sheng et al, 2022 ). These have utilized either one or combination of neuropsychological test scores, neuroimaging, and biofluids.…”
Section: Discussionmentioning
confidence: 99%